High-throughput generation of microfluidic-templating microgels for large-scale single-cell encapsulation - Zhang, Haoyue; Li, Chengze; Zhang, Yujie; An, Chuanfeng; Li, Hanting; Yu, Jiahui; Zhang, Yonghao; He, Wei; Wang, Huanan (Frontiers in Sensors, 2022)
Microfluidics-based fabrication of cell-laden microgels has shown great potential for applications in cell therapy and tissue engineering, however, the difficulty in chip operation and compromised cell viability due to cell sedimentation and channel blockage remain a major challenge for functional cell-laden microgels preparation. Herein, we presented the design and optimization of integrated microfluidic chip for large-scale preparation of cell-laden microgels with controllable size and complex microstructure. Specifically, to avoid severe cell sedimentation and uneven distribution in the parallelized microchannel, we simulated cell movement state using computational fluid dynamics simulation. It was found that higher laminar flow velocity gradient and higher precursor viscosity can significantly improve the uniform cell distribution in parallelized channels and reduce the product difference between channels. Moreover, we designed multiple-layered microfluidic chips allowing multiple inputting liquids for the fabrication of microgels with complex structures. This integrated chip facilitated cell encapsulation at a maximum production rate of 240 ml/h of cell suspension with retained cell viability and functionality. Therefore, our study provided a biocompatible and high-throughput strategy for large-scale preparation of cell-laden microgels, which can enable significant advances for clinical-relevant applications of cell-laden microgels, including cell therapy, tissue regeneration and 3D bioprinting.